Transcranial Magnetic Stimulation Can Improve Cognitive Function and Brain-Derived Neurotrophic Peptide Levels in Post-Ischemic Stroke Patients - Ulima Rahma Asri; Jumraini Tammasse; Andi Kurnia Bintang; Rina Masadah; Muhammad Akbar; David Gunawan Umbas (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Stroke can cause a significant burden of morbidity, including complications of impaired cognitive function. The problem being investigated is hypothesized to be related to brain-derived neurotrophic factor (BDNF), which can be increased by repetitive transcranial magnetic stimulation (rTMS). Purpose(s): To evaluate the effect of Repetitive Transcranial Magnetic Stimulation (rTMS) on serum BDNF levels and cognitive function in ischemic stroke patients. Methods: A pre-test post-test control group, experimental study design, was applied to research conducted at Dr Wahidin Sudirohusodo Makassar and network hospitals in June 2023 until the sample size was met. All ischemic stroke patients who experienced impaired memory function were divided into control (medicamentous, n=10) and treatment (medicamentous + rTMS, n=11). Both at baseline and 14 days following therapy, their BDNF levels and MoCA-INA scores were assessed. ELISA examination is used to measure BDNF levels. The dependent T-test was used to analyze changes in MoCA-INA and BDNF scores in each group. Results: In the treatment group, the median MoCA INA score (26.00 (18.00-28.00) vs. 16.00 (13.00-21.00; p=0.001)) and BDNF levels (1.66 (0.78-3.59) vs. 1.55 (0.01-2.76); p=0.002) increased in two weeks. In contrast, the MoCA-INA score and BDNF levels in the control group did not show a statistically significant difference over a two-week period. MoCA-INA scores and BDNF levels in the treatment group showed a significant and favorable correlation, but not in the control group. Conclusion: rTMS can improve patients' cognitive function after ischemic stroke by improving BDNF levels. Keywords: Brain-derived neurotrophic factor, cognitive function, ischaemic stroke, repetitive transcranial magnetic stimulation